2014
DOI: 10.1200/jco.2013.51.1055
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Risk of Severe, Disabling, Life-Threatening, and Fatal Events in the Childhood Cancer Survivor Study

Abstract: A B S T R A C T PurposeThe first generation of childhood cancer survivors is now aging into their fourth and fifth decades of life, yet health risks across the aging spectrum are not well established. MethodsAnalyses included 14,359 5-year survivors from the Childhood Cancer Survivor Study, who were first diagnosed when they were younger than 21 years old and who received follow-up for a median of 24.5 years after diagnosis (range, 5.0 to 39.3 years) along with 4,301 of their siblings. Among the survivors, 5,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
372
5
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 469 publications
(387 citation statements)
references
References 33 publications
2
372
5
8
Order By: Relevance
“…However, we recently reported that adult cancer survivors had worse overall diet quality than age-and sexmatched controls in the NHANES, and survivorsÕ intake patterns were particularly worse for fiber and empty calories than those in the general population (28). We need to keep in mind that childhood cancer survivors experience a substantially higher chronic disease burden than the general population (2,22,23). Even when diet quality in the survivors and general population is similarly poor, poor diet can have a much larger impact on overall health in long-term childhood cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we recently reported that adult cancer survivors had worse overall diet quality than age-and sexmatched controls in the NHANES, and survivorsÕ intake patterns were particularly worse for fiber and empty calories than those in the general population (28). We need to keep in mind that childhood cancer survivors experience a substantially higher chronic disease burden than the general population (2,22,23). Even when diet quality in the survivors and general population is similarly poor, poor diet can have a much larger impact on overall health in long-term childhood cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…These intake patterns are established risk factors for chronic diseases such as cardiovascular disease, diabetes, and obesity. The remarkably high chronic disease burden and early onset of chronic diseases in this population (2,22,23) reinforce the need to incorporate nutrition into cancer care to improve diet quality and to reduce morbidities in the growing number of children who have survived cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In the Childhood Cancer Survivor Study cohort of over 14,000 survivors, two thirds had at least one chronic condition (e.g., second malignancy, premature cardiovascular disease, endocrinopathy) 25 years postdiagnosis; 3,[5][6][7][8] about half develop a severe or disabling chronic condition. 2,9 Survivors are at increased risk of psychosocial distress (e.g., anxiety, depression, post-traumatic stress), and many have neurocognitive dysfunction. 2,10 Some, particularly those treated with cranial radiation, experience social isolation and struggle in school and the workplace.…”
mentioning
confidence: 99%
“…[1][2][3] For this reason, the Institute of Medicine and others have called for the provision of riskbased survivor-focused medical care that counsels survivors about health risks and screening recommendations tailored to the therapy they received. [4][5][6] However, less than one-third of long-term survivors receive this type of care.…”
Section: Introductionmentioning
confidence: 99%